Strategi Peningkatan Pendanaan Mandiri Panti Asuhan Melalui Pelatihan Sablon - Silvia, Ani; Permana, Budi (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
The purpose of this community service activity is to overcome the problem related to the operational funding needs of an orphanage by creating a small creative industry through the making of screen printing graphic art. The problem arises because the funding source of an orphanage is highly dependent on various sources of social grants that are not fixed so that it is prone to face financial difficulties if the budget expenditure is greater than the source of incoming funds. The solution to solve this problem is to increase economic independence by empowering the youth of the orphanage through the provision of screen printing skills manually. Methods in the implementation of this activity include; pre-implementation phase, implementation phase, and post-implementation phase. Through training and assistance in making screen printing is expected to create economic independence for the orphanage, increase the creativity and can be provision of entrepreneurship for the youth of the orphanage.